(untitled) (International journal of artificial intelligence, 2025)
This article examines the essence of providing socio-psychological assistance to families using foreign experience, social assistance, support and protection for children from problematic families. The author analyzes in detail the socio-psychological aspects of providing psychological assistance to problematic families based on foreign experience.